Specific Features of Internal Waves Manifestation in the Near Mouth Zone of the Danube by High-ResolutionSatellite Data - Medvedeva Alesia; Mikhailichenko Tamara; Stanichny Sergey; Bulatov Vitaly (Russian Journal of Earth Sciences)
The mechanisms of manifestation of internal waves in satellite data of the optical range are considered for the mouth area of the Danube. Three main mechanisms for the manifestation of internal waves are identified – the previously described dynamic (due to a change in the roughness of the sea surface in convergent zones created by a moving internal wave), slick – when surfactants accumulate in convergence zones, and a new one – change in the brightness of the sea surface defined by scattering layer thickness modulation by internal waves. Data from the OLI Landsat-8 scanner for 2015–2019 were used for the analysis. It is shown that in different situations, internal waves can manifest themselves either due to various mechanisms or only due to one of them. Summary maps of manifestations of internal waves in the study area were constructed. Additionally, the situations with quasi-synchronous data of MSI Sentinel-2 and C-SAR Sentinel-1, which displayed the same packets of internal waves, are considered. The selection of such pairs made it possible to estimate the phase velocities of internal waves, which ranged from 0.05 m/s (0.19 km/h) to0.95 m/s (3.43 km/h) in various hydrometeorological situations. Examples of internal wavefront transformation on submesoscale eddies are presented.